2019
DOI: 10.1002/asia.201900577
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regio‐ and Stereoselective Hydrosilylation of Alkynes Catalyzed by Tridentate Cobalt Complexes

Abstract: Severalc obalt complexes bearing tridentate (NNN) ligands were synthesized and served as precatalysts for alkyne hydrosilylation with Ph 2 SiH 2 .F or terminal alkynes, the catalyst L2 b-CoCl 2 was selected, and resulted in the corresponding a-vinylsilanes with high (Markovnikov) regioselec-tivity and extensive functional-group tolerance. For internal diaryl alkynes, the catalyst L2 c-CoCl 2 exhibited the best activity,a nd afforded E-selective vinylsilanes through syn-addition in excellenty ield under mild co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…[78] Thep incer catalysts also exhibited high activities in the selective hydrosilylation of alkynes. [79,80] In 2016, Lu and coworkers described an improved sequential hydrosilylation/ asymmetric hydrogenation of terminal phenylalkynes to obtain chiral silanes using chiral Co-NNN pincer catalysts. After detailed investigations of the steric bulk of substitutents on the pincer ligand, Co-8 was identified as the optimal complex, which exhibited excellent catalytic performance for hydrosilylations of phenylacetylenes with Ph 2 SiH 2 with up to 91 %y ield and > 99 % ee.…”
Section: Catalysts With Pincer Ligandsmentioning
confidence: 99%
“…[78] Thep incer catalysts also exhibited high activities in the selective hydrosilylation of alkynes. [79,80] In 2016, Lu and coworkers described an improved sequential hydrosilylation/ asymmetric hydrogenation of terminal phenylalkynes to obtain chiral silanes using chiral Co-NNN pincer catalysts. After detailed investigations of the steric bulk of substitutents on the pincer ligand, Co-8 was identified as the optimal complex, which exhibited excellent catalytic performance for hydrosilylations of phenylacetylenes with Ph 2 SiH 2 with up to 91 %y ield and > 99 % ee.…”
Section: Catalysts With Pincer Ligandsmentioning
confidence: 99%
“…However, control of stereo‐ and regioselectivity is the major issue hampering the widespread use of this method, largely because three possible hydrosilylation products, namely α‐, β‐(Z)‐, and β‐(E)‐vinylsilanes, can be generated in the hydrosilylation reaction of terminal alkynes, with the former being rarely obtained selectively . By now, some works about the formation of α‐vinylsilane had been published by theorists and experimenters . By inspection of these researches, we found that the metal‐catalysts were mainly introduced for catalyzing this hydrosilylation of alkynes, such as Co, Pt, and Ru .…”
Section: Introductionmentioning
confidence: 99%
“…Vinylsilanes are valuable building blocks in organic synthesis and material chemistry because of their versatile characters, such as low toxicity, high stability, facile manipulations, and a variety of transformations . Accordingly, methods for the preparation of vinylsilanes have gained increased attentions from synthetic chemists, in which the hydrosilylation of alkynes was considered as a simple and straightforward method . This hydrosilylation reaction involves the addition of a Si − H bond across a C − C triple bond, bringing an atom‐economical result with 100% atom efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a desirable catalyst for hydrosilylation of alkenes should be air and moisture stable and operated easily under aerobic conditions. [ 10 ] Very recently, the Chirik [ 11 ] and Nagashima [ 12 ] groups have shown the employment of air‐stable cobalt salts in the hydrosilylation of alkenes, and then Oña‐Burgos group has reported the catalytic hydrosilylation of alkenes under aerobic conditions without solvents and additives by using cobalt(II) carboxylates with terpyridine (tpy) ligand as precursors. [ 10 ] Chen group reported that the synthesis and application of the terpyridines ( NNN ) cobalt complexes with electron‐donating group in the 2‐position of the NNN ring on hydrosilylation.…”
Section: Introductionmentioning
confidence: 99%